Penerapan model pembelajaran langsung untuk meningkatkan hasil belajar matematika siswakelas v sd negeri 014 pematang sikat kecamatan rimba melintang - Antosa, Zariul Antosa Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :Problem background of this research that student do not understand about Math lesson. The average score result of Math test is 25. And only 5 of 20 student or 25% in class can reach standard of KKM, while score of KKM is 70. This is the problem: “Do the Direct Learning Model can improve Math studying result, Students of class V SD Negeri 014 Pematang Sikek Kecamatan Rimba Melintang Kabupaten Rokan Hilir?”. This research form is Observation of Class Action/ Penelitian Tindakan Kelas (PTK). This is the hypothesis of this research: “If the Direct Learning Model is applied therefore gets to increase Math studying results, Student of class V SD Negeri 014 Pematang Sikek Kecamatan Rimba Melintang Kabupaten Rokan Hilir?”. This research is done as much 2 cycles with 6 appointments, there are 4 presentations and 2 times of test. After that, data is collected and made the analyzing. Test I (UH I) shows the increasing average score, from basic score 57 to 72,6, its increase 15,6 points. And at the Test II (UH II) increase about 8,2 points. So that, the average score is to be 80,8. So, total increasing from basic score to Test II (UH II) is 23,8 points. The Classically Completing Activity also increase about 25%, score percentage 25% at the Test I to be 50%. And at the Test II, percentage score is 80%, its increase 30%. Besides that, activity of teacher and student are increasing in every meeting. Percentage of teacher activity at the first meeting is 60%, and at the second is 80% (increase 20%). Fourth meeting, teacher activity is 90% (10%), and 100% at the fifth. Student activity at the first meeting is 55%, and 70% (15%) at the second meeting. There is increasing to be 85% (15%) at the fourth meeting, 95% at the fifth meeting. So, the conclusion is the Implementation of Direct Learning Model can increase Math studying result, Student of class V SD Negeri 014 Pematang Sikek Kecamatan Rimba Melintang. Keywords: Direct Learning Model, Math studying result, PTK.